The Role Of Guidance And Co-Ordination Teachers In Shaping Students' Character (Wiyatamandala, 2025)
The role  of the Counseling Guidance (BK) teacher not only contributes to the resolution of students' academic and personal problems but also forms a strong character and integrity. This is an important foundation in equipping students to face the challenges of life in the future. To find out more about whether the role has been carried out as it should,this research aims to explore the role of Guidance and Counseling (BK) teachers in shaping the positive character of students at SMP Negeri 56 South Jakarta. The background of this research is based on the importance of the role of BK teachers in shaping the personality of students with integrity. The problem raised is how BK teachers can influence the character of students through guidance and counseling approaches. This study uses a qualitative method with data collection techniques in the form of interviews, observations, and documentation. The results of the study show that BK teachers not only help solve students' personal and academic problems but also act as a significant positive behavior model in character formation. The conclusion of the study emphasizes the importance of the role of BK teachers in shaping student honesty, responsibility, and discipline. It is suggested that further research expand the scope of the sample and extend the duration of the study.